2014
DOI: 10.7314/apjcp.2014.15.12.4903
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Decisions to Attend Cervical Cancer Screening among Women Aged 30-60 Years in Chatapadung Contracting Medical Unit, Thailand

Abstract: Background: This study aimed to identify factors associated with women's decisions to attend cervical cancer screening and to explore those linked with intention to attend in the coming year and to continue regular screening. Materials and Methods: A community based case-control study was conducted among woman 30-60 years of age in catchment area of Chatapadung Contracting Medical Unit (CCMU), networking of Khon Kaen Center Hospital, Thailand. Self-administered questionnaires were used to collect data, and in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 12 publications
7
25
2
Order By: Relevance
“…It is well known individuals' knowledge and attitude correlate with their healthcare-seeking behaviors. Other studies concur with our study findings (Birhanu et al, 2012;Saberi et al, 2012;Budkaew and Chumworathayi, 2014).…”
Section: Discussionsupporting
confidence: 94%
“…It is well known individuals' knowledge and attitude correlate with their healthcare-seeking behaviors. Other studies concur with our study findings (Birhanu et al, 2012;Saberi et al, 2012;Budkaew and Chumworathayi, 2014).…”
Section: Discussionsupporting
confidence: 94%
“…However, only 26% had knowledge and only 0.5% had 'good knowledge' with all correct answers. Compared to previous study from one suburb area of the country, only 14% of the women had knowledge about the screening (Budkaew and Chumworathayi, 2014). One factor might be the level of education.…”
Section: Discussioncontrasting
confidence: 59%
“…Aside from the 35% of 'never had' screening, 18% and 4% of Bangkok women had only one test or the last test was more than 5 years, making up 57% of the inadequate screening in our study. Another study from suburb area of Thailand reported 68% of the women had the last screening more than 5 years or inadequate screening by our definition (Budkaew and Chumworathayi, 2014).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the literature, pap smear and HPV knowledge levels, cervical cancer story in family, smoking, suggestion of healthcare workers, sociodemographic factors like especially age, ethnicity, education level, income level, employment status, marital status, use of contraception, number of children, health insurance status, religious and cultural factors were identified as factors affecting having a pap smear test. Again analogously to the results of research, increase in level of knowledge of cervical cancer was noted as one of the factors influencing having pap smear test (Uysal and Birsel, 2009;Erbil et al, 2011;Gulten et al, 2012;Reis et al, 2012;Thulaseedharan et al, 2012;Baskaran et al, 2013;Demirtas and Acikgoz, 2013;Ersin and Bahar, 2013;Gan and Dahlui, 2013;Gyenwali et al, 2013;Karabulutlu, 2013;Shekhar et al, 2013;Budkaew and Chumworathayi, 2014;Sahin et al, 2014;Wongwatcharanukul et al, 2014). Research results and the results expressed in the literature were similar.…”
Section: Discussionmentioning
confidence: 61%